Co-option of the sphingolipid metabolism for the production of nitroalkene defensive chemicals in termite soldiers. (March 2017) - Jirošová, Anna; Jančařík, Andrej; Menezes, Riya C.; Bazalová, Olga; Dolejšová, Klára; Vogel, Heiko; Jedlička, Pavel; Buček, Aleš; Brabcová, Jana; Majer, Pavel; Hanus, Robert; Svatoš, Aleš
Abstract: The aliphatic nitroalkene ( E )-1-nitropentadec-1-ene (NPD ), reported in early seventies in soldiers of the termite genus Prorhinotermes, was the first documented nitro compound produced by insects. Yet, its biosynthetic origin has long remained unknown. Here, we investigated in detail the biosynthesis ofNPD in P. simplex soldiers. First, we track the dynamics in major metabolic pathways during soldier ontogeny, with emphasis on likelyNPD precursors and intermediates. Second, we propose a hypothesis ofNPD formation and verify its individual steps using in vivo incubations of putative precursors and intermediates. Third, we use a de novo assembled RNA-Seq profiles of workers and soldiers to identify putative enzymes underlyingNPD formation. And fourth, we describe the caste- and age-specific expression dynamics of candidate initial genes of the proposed biosynthetic pathway. Our observations provide a strong support to the following biosynthetic scenario ofNPD formation, representing an analogy of the sphingolipid pathway starting with the condensation of tetradecanoic acid withl -serine and leading to the formation of a C16 sphinganine. The C16 sphinganine is then oxidized at the terminal carbon to give rise to 2-amino-3-hydroxyhexadecanoic acid, further oxidized to 2-amino-3-oxohexadecanoic acid. Subsequent decarboxylation yields 1-aminopentadecan-2-one, which then proceeds through six-electron oxidation of the amino moiety to give rise to 1-nitropentadecan-2-one. Keto group reduction and hydroxyl moiety elimination lead toNPD . The proposed biosynthetic sequence has been constructed from age-related quantitative dynamics of individual intermediates and confirmed by the detection of labeled products downstream of the administered labeled intermediates. Comparative RNA-Seq analyses followed by qRT-PCR validation identified orthologs of serine palmitoyltransferase and 3-ketodihydrosphingosine reductase genes as highly expressed in theNPD production site, i.e. the frontal gland of soldiers. A dramatic onset of expression of the two genes in the first days of soldier's life coincides with the start ofNPD biosynthesis, giving further support to the proposed biosynthetic hypothesis. Graphical abstract: Highlights: We investigate the biosynthesis of ( E )-1-nitropentadecene (NPD ) in soldiers of the termite Prorhinotermes simplex . We identify precursors and intermediates ofNPD biosynthesis and study their quantitative dynamics during soldier development. We proposeNPD formation scenario as a co-option and modification of systemic sphingolipid pathway and propose its sequence. We verify the biosynthetic sequence using in vivo incubations of labeled precursors and intermediates. We identify gene orthologs of two enzymes, likely responsible for initial steps ofNPD biosynthesis in soldier frontal gland.